1964
DOI: 10.1071/bi9640798
|View full text |Cite
|
Sign up to set email alerts
|

Short Oommunications Kinins in Germinating Lettuoe Seed

Abstract: The presence, in plants extracts, of factors capable of promoting cell division has been known for some time (Goldacre and Bottomley 1959;Miller 1961) and such compounds have been partially purified (Miller 1961; Zwar, Bottomley, and Kelford 1963). The germination of seeds normally involves cell division as well as cell enlargement (Mayer and Poljakolf-Mayber 1963). Therefore it seemed of interest to investigate whether kinins occur in seeds or are formed during their germination. Lettuce seeds were used beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1965
1965
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…In addition to ABA and GA, cytokinin has been implied to play an important role in regulating seed germination (Barzilai and Mayer, 1964;Khan, 1971;Black et al, 1974;Thomas et al, 1997). Cytokinin is an essential phytohormone involved in the regulation of various aspects of plant growth and development, including seed germination (Werner and Schmülling, 2009).…”
mentioning
confidence: 99%
“…In addition to ABA and GA, cytokinin has been implied to play an important role in regulating seed germination (Barzilai and Mayer, 1964;Khan, 1971;Black et al, 1974;Thomas et al, 1997). Cytokinin is an essential phytohormone involved in the regulation of various aspects of plant growth and development, including seed germination (Werner and Schmülling, 2009).…”
mentioning
confidence: 99%
“…In the classical photosensitive material, achenes oí Lactuca sativa L. cv. Grand Rapids, Barzilai & Mayer (1964) found cell division promoting substances, particularly after 48 h germination. The same coincidence between increased cytokinin activity and radicle emergence has been documented also for a number of photoinsensitive species such as Acer (Julin-Tegelman & Pinfield, 1982), and Rosa (Julin-Tegelman, 1983).…”
Section: Discussionmentioning
confidence: 98%
“…Barzilai and Mayer (1964) were unable to detect cytokinins in dry lettuce seeds. Van Staden (1973a) later showed that cytokinins were present in dry lettuce seed, but in a bound, water‐soluble storage form.…”
Section: Discussionmentioning
confidence: 99%
“…Barzilai and Mayer (1964) were unable to detect any cytokinins in dry lettuce seeds. These compounds did appear during germination.…”
Section: Introductionmentioning
confidence: 99%